Exploring the Significant Factors Influencing Bussiness benefit in Construction Sector - Ladika Ladika; Johan Budiman; Syafwandi Syafwandi; Asri Nurhafsari (Institute of Computer Science (IOCS), 2022)
Stakeholders capability factors can be effect by domination and competency beside their interpersonal skills to gain competitive advantage organizations need to have something that the competitors do not have and cannot achieve in the short-term. Bussiness benefit in construction sector must have stakeholders with the competency and domination for knowledge the project characteristic to be the project success. This research based on 80 samples from the stakeholders in business construction sector wich which will be analyzed with the partial structural-least square equation model (PLS-SEM). The result of the analysis show that the competency an domination of the Stakeholders is the only variable consistently giving influence upon the project success, project characteristic and business benefit in construction sector in all modelling compositions.